THE USE OF ELECTRONIC EVIDENCE AS MEANS OF PROOF IN ADMINISTRATIVE COURT PROCEEDINGS - Shevchenko, Taras (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: the study aims to provide a comprehensive analysis of the legal nature and specific features of using electronic evidence in administrative court proceedings in Ukraine under the conditions of digital transformation of justice. Methods: the research applies a comparative legal analysis of electronic evidence and traditional means of proof (written, material, and witness testimony), a systematic approach to evaluating the provisions of the Code of Administrative Procedure of Ukraine, as well as an analysis of judicial practice and international standards (Regulation eIDAS). Discussion: the paper identifies key issues related to the classification, authenticity, and admissibility of electronic evidence, along with the lack of unified procedural standards. It examines controversial aspects of the evidential value of e-mails, screenshots, audio and video recordings, and emphasizes the role of a qualified electronic signature as a guarantee of data authenticity. Results: the findings highlight the need for a comprehensive combination of legal and technical safeguards, the unification of rules for submission and evaluation of electronic evidence, and the harmonization of national practice with international standards of digital justice. Recommendations are proposed for improving legislation and enhancing the digital competence of legal professionals. The article it shows that the emergence and active use of electronic evidence is a natural consequence of the development of information technologies, the expansion of electronic communications, and the introduction of electronic services in the activities of public authorities. It is determined that electronic evidence differs significantly from traditional types of evidence in its intangible nature, dependence on technical means for reproduction, the possibility of existing in several identical copies, and the need for special authentication procedures. A comparative analysis of electronic evidence with written, material, and witness testimony has been carried out, which has made it possible to substantiate its intermediate nature and uniqueness as an independent institution of evidence law. Particular attention is paid to the requirements of the Code of Administrative Procedure of Ukraine regarding the relevance, admissibility, reliability, and sufficiency of evidence, as well as the peculiarities of the court’s assessment of electronic evidence based on internal conviction. The problems of practical application are highlighted, including the lack of a unified classification, ambiguity in defining the boundaries between electronic documents and electronic material evidence, as well as the fragmentary nature of judicial practice. The paper emphasizes the importance of using a qualified electronic signature as a guarantee of data authenticity and a means of confirming the authorship of electronic documents. At the same time, it outlines the problem of the evidential value of e-mails, screenshots, audio and video recordings, which remain the most common, but not always clearly regulated means of evidence. Conclusions have been formulated regarding the need for a comprehensive combination of legal and technical safeguards, as only their interaction can ensure the relevance, admissibility, and reliability of electronic evidence in court proceedings. Such a balance minimizes the risks of falsification or modification of digital data and, at the same time, guarantees effective protection of the rights of participants in administrative proceedings. The article reveals both theoretical and legal and practical aspects of the use of electronic evidence, offering a holistic view of its place and significance in administrative proceedings and forming scientifically sound recommendations for the further development of the institution of electronic evidence.